Investigation of beryllium diffusion in HVPE-GaN grown in [11–20] and [10-10] crystallographic directions. (1st March 2022) - Sierakowski, Kacper; Jakiela, Rafal; Fijalkowski, Michal; Sochacki, Tomasz; Iwinska, Malgorzata; Kempisty, Pawel; Turek, Marcin; Bockowski, Michal
Abstract: The diffusion of beryllium in gallium nitride crystals grown in non-polar crystallographic directions by halide vapor phase epitaxy was investigated. The layers were crystallized on (10-10) and (11–20) planes of native ammonothermal substrates of the highest structural quality. The new-grown crystals were prepared to an epi-ready state, implanted with beryllium, and treated with ultra-high-pressure annealing. The crystallographic structure of all the samples before and after ion implantation as well as annealing processes was evaluated by X-ray diffraction measurements. The diffusion of beryllium was investigated by analyzing depth profiles obtained by secondary ion mass spectrometry. The diffusion profiles were box-shaped for both examined non-polar directions. Pre-exponential factors and activation energies for beryllium diffusion in non-polar gallium nitride were determined. A model related to point defect complexes, based on gallium vacancies and oxygen, was proposed for explaining the box-shaped beryllium diffusion profiles and the visible differences in the diffusion range between the two analyzed non-polar directions. Highlights: Diffusion of implanted Be was for the first time examined in non-polar GaN. Box-shaped Be depth profiles (very different than for the [0001] direction) were observed by secondary ion mass spectrometry for [10-10] and [11–20] directions. The diffusion range of Be was higher for the [11–20] than the [10-10] direction. Temperature-dependent diffusion coefficients of Be in GaN and activation energies were determined. Higher oxygen concentration increases the Be solubility in gallium nitride due to possible creation of complex defects.